IMPACT OF TRAINING AND DEVELOPMENT ON EMPLOYEE SATISFACTION IN HOSPITALITY SECTOR: A STUDY OF HOTEL EMPLOYEES IN KERALA WITH SPECIAL REFERENCE TO KOTTAYAM DISTRICT - N S, Surya; Jaikumar, Padmaja (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research explores the relationship between training and development initiatives and employee satisfaction in the hotel industry, focusing on hotels in Kerala. Employing a mixed-methods approach, the study collected data through structured surveys and interviews with hotel employees and management. Results indicate that effective training programs, including technical, leadership, and soft skills development, significantly enhance employee satisfaction. Critical factors influencing satisfaction include clear career advancement opportunities, a balanced work-life environment, and a supportive learning culture. The study also highlights challenges such as resource limitations and operational constraints, offering recommendations to address these issues and enhance training effectiveness. The findings provide valuable insights for improving employee engagement, retention, and overall organizational performance in the hospitality sector.